Incidence of umbilical cord around the neck and its eﬀects on mode of delivery and fetal outcome at tertiary care hospital - Nandhini, S.; Anuradha, C. R.; Renuka, S.; Vijayalakshmi, K.; Sailatha, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Umbilical cord is one of the fetal membranes. It is developed from the yolk sac. Umbilical cord is tubular structure. Approximate length of the cord is 50 cm. Umbilical cord around the neck is called as the nuchal cord. The aim of the study is to find out the incidence of umbilical cord around the neck at the time of delivery and its fetal outcomes. Methods: It is a retrospective observational study. This study was conducted in the department of obstetrics and gynecology at a tertiary care hospital over a period of 6 months (Feb-Jul 2020). Out of 542 patients, 388 were enrolled in this study after the inclusion and exclusion criteria, of which 101 were delivered with umbilical cord and the remaining were 287 patients in control group. Results: Present study showed 38.4% incidence of umbilical cord at the time of delivery. Incidence is more among the primigravida and it is statistically significant. Both intrapartum and postpartum risks are not related to umbilical cord around the neck. Mean length of the cord in patients delivered with cord around the neck is more when compared to the control group and has significant p value. Conclusions: This study concludes that the presence of umbilical cord, alone is not an indication for caesarean section. Umbilical cord with 3 loops was associated with increased operative delivery and low Apgar score, proper intrapartum surveillance and portogram leads to good fetal outcome.